IMPLEMENTASI MANAJEMEN PEMASARAN HIJAU DI DALAM INDUSTRI MINYAK KELAPA SAWIT DI NEGARA INDONESIA - Riza M. Yunus (Jurnal Kelola: Jurnal Ilmu Sosial, 2019)
The palm oil industry has always been a fairly complicated problem. This is because discussions about the palm oil industry will bring up issues such as the destruction of nature, human rights, and forest fires. Therefore, this study aims to see how the application of green marketing management can help improve the strategic tools and sustainability of the palm oil industry business. The research method that will be used is qualitative research. The data used by the researcher comes from the results of research or studies that still have similarities in discussing green marketing management. The results of this study found that green marketing strategies can help the palm oil industry to be able to maintain its business continuity. However, for this strategy to be implemented properly, it is necessary to have a relationship that exists between business owners and different stakeholders.